Accuracy of endodontic working length determination using cone beam computed tomography. (15th November 2013) - Connert, T.; Hülber‐J, M.; Godt, A.; Löst, C.; ElAyouti, A.
Abstract Aim To evaluate the accuracy of endodontic working length (WL) measurements by cone beam computed tomography (CBCT). Methodology Forty‐two extracted human teeth were placed into three full jaw models. Preoperatively, CBCT scans of the models were performed (voxel size: 0.2 mm). Endodontic access cavities were prepared, and the coronal third of 70 root canals were pre‐flared. The real WL was measured by inserting a K‐file into the root canal until the tip was visible at the foramen, a silicon stopper was adjusted to the corresponding cusp tip, and the length was measured using a micrometer. CBCT WL was simply measured by tracing a line between the apical foramen and the corresponding cusp tip. When the foramen and cusp tip were not visible in one plane, the measurement was taken in two planes. To quantify measurement error, real and CBCT WLs were repeated four times by two experienced operators. Paired analysis for each variable was performed, and the mean of absolute differences and the corresponding 99% confidence intervals were calculated. The t‐test was used for comparison. Results The coefficient of repeatability, reproducibility and interoperator agreement were <0.5 mm. CBCT measurements were accurate; the mean of absolute differences between CBCT and real WL was 0.41 mm (99% CI 0.31–0.52 mm). Conclusion Using a simplified method, CBCT images of 0.2 mm voxel size can be used to accurately determine endodontic WL.